PEMANFAATAN PERANGKAT TEPAT GUNA BANTUAN BANK INDONESIA DI KAMPUNG TEMATIK “BRILLIANT” BOJONG RENGED, KECAMATAN TELUKNAGA KABUPATEN TANGERANG - Bonar BJ Napitupulu; Francisca Sesri Goestjahjanti; Dwi Ferdyatmoko Cahya Kumoro; Istajib Kulla Himmy Azz; Jaka Suwita; Sucipto Basuki; Shofwatun Hasna (Jurnal Abdi Inovatif : Pengabdian kepada Masyarakat, 2025)
Abstract Waru Brilliant Thematic Village, located in Bojong Renged, Teluk Naga District, Tangerang Regency, is one of the best thematic villages that successfully obtained a grant from Bank Indonesia (BI) in 2024. This village previously faced challenges in increasing productivity and community welfare due to limited equipment that supports local economic activities, especially in the agricultural and food processing sectors. The lack of appropriate tools is a significant obstacle in optimally developing village potential in terms of food security and community economic empowerment. Through a grant in the form of proper tools from BI, efforts to improve welfare, food security, and the local economy have begun to be realized. Universitas Insan Pembangunan Indonesia (UNIPI) facilitates and moderates the entire series of activities, from training on the use of tools to assistance in implementing the technology in the field. This activity's implementation method begins with identifying problems in the community, followed by the preparation and submission of a grant proposal to BI. After the proposal is approved, a grant is handed over in the form of appropriate tools to the community, which is then followed by the implementation stage and technical training on the use of the tools. UNIPI also actively assists the adaptation and application of the technology to ensure the program's success. This paper elaborates on the program's process, impact, and sustainability, highlighting the transformative role of appropriate technology in community development. Keywords: thematic village, food security, community development, appropriate technology Abstrak Kampung Tematik Waru Brilliant di Bojong Renged, Kecamatan Teluk Naga, Kabupaten Tangerang, berhasil memperoleh hibah dari Bank Indonesia (BI) pada tahun 2024. Kampung ini sebelumnya menghadapi tantangan dalam meningkatkan produktivitas dan kesejahteraan masyarakat akibat keterbatasan peralatan yang mendukung kegiatan ekonomi lokal, khususnya dalam sektor pertanian dan pengolahan hasil pangan. Kurangnya alat tepat guna menjadi hambatan utama dalam mengembangkan potensi kampung secara optimal, baik dari sisi ketahanan pangan maupun pemberdayaan ekonomi masyarakat. Melalui hibah berupa alat tepat guna dari BI, upaya peningkatan kesejahteraan, ketahanan pangan, serta perekonomian lokal pun mulai diwujudkan. Universitas Insan Pembangunan Indonesia (UNIPI) memfasilitasi dan memoderasi seluruh rangkaian kegiatan, mulai dari pelatihan penggunaan alat hingga pendampingan implementasi teknologi tersebut di lapangan. Metode pelaksanaan kegiatan ini dimulai dari proses identifikasi permasalahan di masyarakat, dilanjutkan dengan penyusunan dan pengajuan proposal hibah ke BI. Setelah proposal disetujui, dilakukan penyerahan hibah berupa alat tepat guna kepada masyarakat, yang kemudian diikuti tahap implementasi serta pelatihan teknis penggunaan alat. UNIPI juga secara aktif mendampingi proses adaptasi dan penerapan teknologi tersebut untuk memastikan keberhasilan program. Tulisan ini mengelaborasi proses, dampak, dan keberlanjutan program, menyoroti peran transformatif teknologi tepat guna dalam pembangunan masyarakat. Kata Kunci:  kampung tematik, ketahanan pangan, pembangunan masyarakat, teknologi tepat guna